Radiographic assessment of agenesis of the third molars: A cross-sectional study - Nithiyasri Ganesan; T Maheswaran; Ganapathy Nalliyapan; Ilayaraja Vadivel; Dineshshankar Janardhanam; Yoithap Prabhunath Thuckanaickenpalayam Ragunathan (Wolters Kluwer Medknow Publications, 2023)
Congenital absence of a tooth is known as dental agenesis or agenesis of a tooth. Although both deciduous and permanent dentition are prone to agenesis, permanent third molars are the most commonly affected teeth. Aim: The aim of this study was to estimate the prevalence of third molar agenesis in the South Indian-based population. Materials and Methods: Three hundred subjects (150 males and 150 females) with a range between 18 and 25 years who had no previous history of third molar extractions and who had other dental complaints that required radiographic investigation using orthopantomograms were selected for the study. The digital radiographs were assessed for the identification of third molar agenesis. The data such as gender and presence of third molar agenesis and site were recorded and statistically tested using the Chi-squared test. Results: The prevalence of third molar agenesis in the studied population was 24.3%. Agenesis of third molars is more prevalent in females than males (P = 0.001). However, there was no significant difference noted between the right and left maxillary and mandibular third molars among males and females (P > 0.05). Conclusion: Based on our findings, third molars are found to be highly vulnerable to dental agenesis, especially in females.